A Comparative Analysis of Amytripiline, Flunnarazine and Topiramate in the treatment of Primary Headache - Pokharel, Babu Ram; Sharma, Gopal Raman; Upadhyaya, Prabhaw; Budhathoki, Samip Jung; Thapa, Santosh; Koirala, Jyoti (Nepal Journal of Neuroscience, 2021)
Introduction Primary headache disorder, characterized by recurrent headache is the most prevalent disease leading to widespread ill health and impaired quality of life. In Nepal headache is one of the most common cause of patient attending neurology clinic. Amitriptyline, Flunarizine and Topiramate are common drugs in the treatment of primary headache. We conducted this study to compare the efficacy of drugs namely Amitriptyline, Flunarizine and Topiramate in the treatment of primary headache Materials and Methods This is the retrospective data analysis of primary headache patient treated with amitriptyline, flunarizine and topiramate. On their first, second and third subsequent visits, Headache Impact Test 6 Scoring was done by a medical person. Patient were treated clinically. After third follow up data were analyzed using SPSS version 20.0. Categorical variables were compared by chi-square test, paired sample t-test, ANOVA test and Welch test. Results A total of 142 patient data was analyzed. The most common age group were between 20 to 39 years (56.34%) followed by 40 to 59 years (33.80%). Female were predominant in the group 124 (87.32%). All three medication Amitriptyline, Flunarizine and Topiramate were able to significantly lower Headache impact test -17.23 ± 6.643, -14.06 ± 7.155, -15.82 ± 5.907 respectively (P- <0.001). Amitriptyline was found to be better than other two drugs in reducing Headache Impact Test. Conclusion All three drugs namely Amitriptyline, Flunarizine and Topiramate, are significantly effective in the treatment of primary headache. Though tension type of headache is the most common type of headache, amitriptyline seems to be equally effective in treatment with other primary headaches.